Understanding the Economics of Aphasia: Recent Findings from Speech and Language Research - Jacobs, Molly; Ellis, Charles (Seminars in Speech and Language, 2022)
In recent years, stakeholders engaged in the study, treatment, and understanding of aphasia outcomes have emphasized the need for greater transparency regarding the economics of aphasia rehabilitation. Most notably, third-party payers and clinicians have a keen interest in understanding the resources used to treat aphasia, particularly the cost-effectiveness and value of aphasia treatments. In this article, we review the current literature related to the economic burden of aphasia and the cost and cost-effectiveness of aphasia treatments. To date, relatively few scholars have attempted to study the efficiency, scale, and scope related to the economics of aphasia and the cost-effectiveness of aphasia treatment. While studies of the cost-effectiveness of aphasia treatments have shown rehabilitative treatments conform to established quality and cost benchmarks, the continued progress and developments in the treatment of aphasia and measurement of clinical outcomes has left many areas unstudied. We highlight the need for greater emphasis on the cost-effectiveness of aphasia treatments in addition to the traditional focus on the efficacy of treatment outcomes.
Keywords: aphasia; economics; cost-effectiveness; value